Preparation and Characterization of Isolated Polyvanadate Containing Mn2+ and W6+ Hetero Ions - Kumar Thakur, Alok; Kumar, R.; Jha, R.R. (Asian Journal of Chemistry, 2013)
One new triheteropoly complex was synthesized containing two hetero cations Mn2+ and V6+ substituted in the polyvanadate anion having composition [V9O27]9-. The product obtained was dull yellow in appearance. Infrared spectral analysis of the product suggest the presence of Na+, W=O, V=O, V-O, Mn-O, W-O-W and W-Mn along with hydrogen bonded H2O group in the complex. The flame photometric experiment also indicates the association of sodium with the complex as a golden yellow flame was obtained on heating the product in flame photometer. The molecular weight determination of the triheteropoly complex by cryoscopic method was almost in accordance with the calculated result of the isolated product. The stability of the isolated triheteropoly vanadate complex was determined by applying thermogravimetric and differential thermal analysis. The results of the both types of thermal analysis suggest the thermal stability of the complex in the air at room temperature. The composition of the residue product on the basis of elemental analysis is assigned as Na[MnWV9O27]9H2O.